2017
DOI: 10.1016/j.jval.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative Colitis Treatment Patterns and Cost of Care

Abstract: Objectives: To examine treatment patterns, dosing, health care resource utilization, and cost of tumor necrosis factor inhibitors (TNFi), adalimumab (ADA) and infliximab (IFX), among patients enrolled in US Humana insurance plans who have been diagnosed with ulcerative colitis (UC). Methods: This retrospective cohort study identified the first pharmacy or medical claim for ADA or IFX (from January 1, 2007, to December 31, 2014) in patients with continuous enrollment for 6 months or more preindex and 12 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 15 publications
1
27
0
1
Order By: Relevance
“…The median duration of biologic treatment among treatment-naïve patients in the current study was 7.2 months, and 64.5% of those who received biologics discontinued after 1 year. Null et al, in a retrospective analysis of US health claims data, reported that about 50% of patients receiving infliximab or adalimumab discontinued during the first 12 months, and a substantial percentage of those patients did not restart or switch to another biologic therapy [ 29 ]. The reasons for discontinuation, though poorly understood, may include side effects or a lack of efficacy [ 30 ], although the reasons for discontinuation were unavailable in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The median duration of biologic treatment among treatment-naïve patients in the current study was 7.2 months, and 64.5% of those who received biologics discontinued after 1 year. Null et al, in a retrospective analysis of US health claims data, reported that about 50% of patients receiving infliximab or adalimumab discontinued during the first 12 months, and a substantial percentage of those patients did not restart or switch to another biologic therapy [ 29 ]. The reasons for discontinuation, though poorly understood, may include side effects or a lack of efficacy [ 30 ], although the reasons for discontinuation were unavailable in our study.…”
Section: Discussionmentioning
confidence: 99%
“…One retrospective database study of TNF inhibitor use reported 12-month discontinuation rates with adalimumab and infliximab of 52% and 45%, respectively. 34 …”
Section: Discussionmentioning
confidence: 99%
“…The results of the histopathological analysis showed that the DSSinduced pathological changes were significantly improved by nigeglanine treatment. ZO-1 and occludin levels were significantly reduced during the progression of DSS-induced UC; however, upon have attracted increasing attention with regards to the prevention and control of many diseases, especially digestive diseases (Null et al, 2017).…”
Section: Nigeglanine Modulates Zo-1 and Occludin Expression In Dss-induced Colitismentioning
confidence: 99%